2015
DOI: 10.1007/s00572-015-0650-7
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal symbiosis and methyl jasmonate avoid the inhibition of root hydraulic conductivity caused by drought

Abstract: Hormonal regulation and symbiotic relationships provide benefits for plants to overcome stress conditions. The aim of this study was to elucidate the effects of exogenous methyl jasmonate (MeJA) application on root hydraulic conductivity (L) of Phaseolus vulgaris plants which established arbuscular mycorrhizal (AM) symbiosis under two water regimes (well-watered and drought conditions). The variation in endogenous contents of several hormones (MeJA, JA, abscisic acid (ABA), indol-3-acetic acid (IAA), salicylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 64 publications
5
54
0
Order By: Relevance
“…However, under drought stress the drought-tolerant genotype maintained a higher L o values by 360% as compared to drought-sensitive genotype. Interestingly, AM increased L o under drought compared to control plants in both genotypes, and this enhancement is in accordance with previous studies on AM plants under drought (Porcel et al, 2005; Bárzana et al, 2014; Sánchez-Romera et al, 2016). The increase of L o in AM plants could be related to an increased expression of plant or fungal aquaporins (Sánchez-Romera et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, under drought stress the drought-tolerant genotype maintained a higher L o values by 360% as compared to drought-sensitive genotype. Interestingly, AM increased L o under drought compared to control plants in both genotypes, and this enhancement is in accordance with previous studies on AM plants under drought (Porcel et al, 2005; Bárzana et al, 2014; Sánchez-Romera et al, 2016). The increase of L o in AM plants could be related to an increased expression of plant or fungal aquaporins (Sánchez-Romera et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, AM increased L o under drought compared to control plants in both genotypes, and this enhancement is in accordance with previous studies on AM plants under drought (Porcel et al, 2005; Bárzana et al, 2014; Sánchez-Romera et al, 2016). The increase of L o in AM plants could be related to an increased expression of plant or fungal aquaporins (Sánchez-Romera et al, 2016). However, fungal aquaporins seem not to be involved in such increase since one gene was unaltered by drought, another gene was inhibited considerably in both maize cultivars, and the third one was only slightly induced in the drought-sensitive cultivar, but inhibited in the drought-tolerant one.…”
Section: Discussionsupporting
confidence: 92%
“…Saia et al (2014) recently demonstrated that, in field conditions, berseem clover (Trifolium alexandrinum) AM plants subjected to water deficit can better tolerate the negative impact of drought stress on plant growth in combination with a stimulated N 2 fixation. A regulation of the root hydraulic properties during AM symbiosis also has been reported Bárzana et al, 2012;Sánchez-Romera et al, 2015). Bárzana et al (2012) demonstrated an ability of AM plants to modulate the switch from apoplastic water flow to a cell-to-cell pathway (which involves the transport of water across membranes and the regulation of aquaporin genes), suggesting that AM fungal colonization may allow plants to better respond to water demands from the shoot upon water stress (WS) conditions.…”
mentioning
confidence: 83%
“…AM symbiosis and methyl jasmonate (MeJA) prevented the inhibition of root hydraulic conductivity in Phaseolus vulgaris exposed to DS, probably through a reduction in root salicylic acid concentrations38. In addition, under unfavourable conditions, plants might stimulate increased strigolactone production to promote symbiosis to deal with the stress8.…”
mentioning
confidence: 99%
“…In addition, under unfavourable conditions, plants might stimulate increased strigolactone production to promote symbiosis to deal with the stress8. Mycorrhizal P. vulgaris plants had relatively higher indole-3-acetic acid (IAA) and abscisic acid (ABA) levels than non-mycorrhizal controls under well-watered (WW) and DS conditions38. Little is known about the response of phytohormones to mycorrhization under DS and the subsequent regulation of root morphology by these phytohormones.…”
mentioning
confidence: 99%